Design of Emergency Medical Record Form Based On Hospital Accreditation Standard Version 2012 in Hospital “X” - Atma Deharja; Selvia Juwita Swari; Dyah Eriyaning Esti (Universitas Muhammadiyah Yogyakarta, 2017)
Based on pre-survey in Balung General Hospital, showed that emergency form has not qualified with hospital accreditation standard (version 2012) for an early medic and nursing assessment. The aim of this research is to re-design emergency forms based on hospital accreditation standard (version 2012) in Balung General Hospital. This research is a qualitative study with observation, interview, and brainstorming. The result of this research is viewed from the physical aspect of the emergency form using white paper in size of A4 80 gram in portrait layout. Based on anatomy aspect, the form heading is to put the logo, the name and the full address of the instance, the introduction which should be appropriate with the aim of the form that is the early medic and nursing assessment. Based on the content aspect of the emergency form, the additional data consists of a kind of triage, the date of arrival and handling, painful scale, medicine allergic and fall down risk. Based on the nursing assessment form, it consists of patient's identity, primary survey, secondary survey, nursing diagnose, action plan, self nurse-act, nursing evaluation, further action, given tasks and nurse authentication. Hopefully, the researcher's suggestion related to the result of emergency form design can be applied in Balung General Hospital, Jember.